The Influence of Organizational Culture and Work Motivation on the Work Productivity of Gen Z Employees - Nurhidayah, Ami (Lentera Ilmu Nusantara, 2025)
This study aims to determine the Influence of Organizational Culture and Work Motivation on the Work Productivity of Gen Z Employees. The results of the validity and reliability test show that all variables and indicators are valid and reliable. The results of the heteroscedasticity test, F test, Descriptive Statistics test, The results of heteroscedasticity showed that there was no heteroscedasticity, the independent variables did not have a joint effect on the dependent variables, and the variables had a stronger relationship with the dependent variables, but the effect remained insignificant. However, based on the Determination Coefficient test, it shows that the R value of 0.994 shows a very strong (almost perfect) relationship between independent and dependent variables. With a score of 98.8%, the rest is likely to be influenced by other factors that were not studied in this study.